The international labor standard on the elimination of discrimination in employment: Response and prospect of Malaysia - Abdul Wahab, Harlida (World Academy of Science, Engineering and Technology, 2013)
Discrimination in employment has its wider social and economic consequences other than mere violating a basic human right. Discrimination involves treating people differently because of certain grounds such as race, color, or sex, which results in the impairment of equality of opportunity and treatment.As an essential part of promoting decent work, combating discrimination through the principle of non-discrimination has been established by the International Labor Organization (ILO) through the Declaration on Fundamental Principles and Rights at Work 1998.Considering elimination of discrimination in employment as a core labor standard, member states are expected to respect, promote and implement it to their national laws and policies.Being a member state, Malaysia has to position herself align with this international requirement. The author discusses the related convention together with Malaysia-s responses on the matter.At the closing stage, the prospect of Malaysia is presumed taking into account of the current positions and reports submitted to the ILO.